Maringá líquida : o projeto da cidade, as águas urbanas e a ecologia da paisagem - Vasconcelos, Gustavo Bruski de (2010)
This study is an investigation on the relationship between the town and the natural environment, in which it takes an approach to the original layout of Maringá, carried out by Jorge Macedo Veira, through an ecological trough. Thus, this research considers that Maringa´s planner conveyed environmentaly friendly urban features, namely water supply and drainage. As a result, it is stated that the urban landscape built in Maringá has antecipated some aspects of what has recently been called sustainability. The virtues founded in this layout, yet little recognized, can contribute for the elaboration of new urban designs.